An Overview of the Chemistry and Utilization of Detergents, both Soap and Non-Soap - Kabir, Fatima Mohammad; Uduma, A. U.; Uduma, Maria B. (Journal of Science Research and Reviews, 2024)
This analysis explores the fundamental contrasts between detergent soaps and non-soap detergents, concentrating on their chemical makeup, cleaning methods, environmental impact, and applicability for diverse uses. Traditional soaps are made from natural fats and oils, which results in a biodegradable cleaning agent. Non-soap detergents, on the other hand, are made synthetically and frequently have better cleaning capabilities, but their limited biodegradability may cause environmental issues. In order to determine the best option depending on particular cleaning requirements, this study examines the trade-offs between these two cleaning chemicals, taking into account variables including water hardness, skin sensitivity, and sustainability consequences. According to this overview, the dynamic development, formulation, and use of soaps and soapless detergents are primarily driven by chemistry and chemical principles. The aim of this study therefore, is to conduct extensive survey on the chemistry and utilization of detergents, both soap and non-soap.
Keywords: Biodegradability; Cleansing efficiency; Detergent; Hard water; Soap